Why security science? - Akrap, Gordan (Array, 2020)
In this paper, the authors are discussing the need to introduce security sciences as a new scientific field within the existing organization of social sciences. The development of quality, usable, and functional human knowledge and skills have been guaranteed safe and undisturbed development of individuals and communities since the beginning of their existence. The development of society has led to a change of paradigms on which reflections and analyses about security, conflict and war rested. This, in turn, brings us to the situation of the need to change those paradigms of organization, principles, concepts, and theories of security as a new scientific discipline that should enable the continuation of safe and unhindered development of human society.